2014
DOI: 10.7314/apjcp.2014.15.20.8941
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Awareness among Turkish Nursing Students

Abstract: Background: This study conducted to determine breast cancer awareness and influencing factors among nursing students in the West Black Sea Region in Turkey. Materials and Methods: This cross-sectional descriptive study was conducted between April-May, 2014. The sample was 270 female nursing students. Data were collected by Personal Information Form and Champion's Health Belief Model Scale (CHBMS). Results: The students' mean age was 21.6±2.09 and 81.1% had knowledge about breast cancer from their academic educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 30 publications
3
19
1
1
Order By: Relevance
“…Results of some studies about the health belief level for breast cancer in Turkey are similar to the findings of this study (22,29). Our students' obstacles perception scores are low and their self-efficacy perception scores are high when compared to the study by Gerçek et al (30).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Results of some studies about the health belief level for breast cancer in Turkey are similar to the findings of this study (22,29). Our students' obstacles perception scores are low and their self-efficacy perception scores are high when compared to the study by Gerçek et al (30).…”
Section: Discussionsupporting
confidence: 78%
“…The findings of our study are more positive than the study conducted by Çelik et al (29) in terms of health beliefs. Lavdaniti (32) has reported that the students' perception of obstacles is low and that their perception of seriousness is high.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Moreover, a positive family history may influence the knowledge, attitude, and practice of women and young girls regarding breast cancer and related screening. In line with this, (Celik et al, 2014) identified a positive relation between nursing students' awareness of breast cancer and BSE and a positive family history among them. The present study assessed students' knowledge of breast cancer and BSE before implementation of the educational program.…”
Section: Discussionmentioning
confidence: 55%